Ludic strategy for promoting engagement of parents and caregivers in the safety of pediatric patients - Karyne Maria de Morais Gonçalves; Maria Tereza Teles Coelho Aguiar Costa; Débora Caixeta Bernardes Silva; Manuela Estrela Baggio; Allana dos Reis Corrêa; Bruna Figueiredo Manzo (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To evaluate a ludic strategy developed to promote the engagement of parents and caregivers in the pediatric patient safety actions. Method: A qualitative research developed in the action-research modality, using the thematic content analysis method for data treatment, developed with caregivers of children admitted to the pediatric unit of the public hospital of Belo Horizonte, Minas Gerais, between May and October 2018. Results: Three thematic categories emerged: Learning about patient safety through the game; Game evaluation as a ludic strategy in promoting patient safety and; Change of perception and behavior of parents and caregivers in safety promotion actions. Conclusion: The game was deemed as an important tool for patient safety knowledge transfer, motivating parents and caregivers to become more critical and more co-participant as for the hospitalized child care.